Al-Qur'an Perspective About Ijarah (Leasing) - Abdul Khaliq Khaliq; Achmad Abubakar; Rusydi Khalid (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Ijarah is a rental wage given to someone who has done a job in return for his work. This study aims to describe the substance of ijarah in terms of etymology, terminology and the use of the word ijarah in the Qur'an and the study of interpretation, the meaning of the word ijarah in the Hadith, and the Ijma' of scholars related to ijarah. Research on ijarah in the Qur'an has been carried out by many Al-Qur'an reviewers both in terms of its meaning in language or terms as well as in terms of its implementation. This study uses descriptive-analytic research and library research. The results of this study showed that the word ijarah was found in the Qur'an 6 times, namely in Surah Al-Baqarah verse 62, Surah Al-Qashash verse 26, Surah At-Thalaq verse 6, Surah Al-Mu'minuun verse 72, Surah Al-An'am verse 90 and Surah Yusuf verse 104.